KONSEPSI RELASI SOSIAL DALAM PERSPEKTIF AL-QUR’AN - Aas Siti Sholichah (Institut PTIQ Jakarta, 2019)
Appreciation of the Qur'an in social relations is implied in the QS. Al-Hujurat / 49: 13. In this verse Allah SWT created tribal men, women, nationalities, different languages, even each human being has differences both physically and personally. The purpose of human creation is to get to know one another, which can form a fabric of cooperation and synergy. Mutual respect and respect in different beliefs, nations, tribes, and countries are also different languages, so as to create peace and tranquility in social life.